Mechanism of Carbon Dioxide Adsorption in a Highly Selective Coordination Network Supported by Direct Structural Evidence1. Issue 6 (11th December 2012) - Plonka, Anna M.; Banerjee, Debasis; Woerner, William R.; Zhang, Zhijuan; Nijem, Nour; Chabal, Yves J.; Li, Jing; Parise, John B.
<x xml:space="preserve">Abstract</x> Trapped in a porous material: The position of adsorbed CO2 in a nanoporous coordination framework was determined using a combination of techniques including single‐crystal X‐ray diffraction, in situ X‐ray powder diffraction coupled with differential scanning calorimetry, and theoretical calculations. The study reveals that the adsorbed CO2 stays in a "pocket" between two phenyl rings, interacting with the aromatic electron density (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>